The pursuit of the Nazi mind : Hitler, Hess, and the analysts - Pick, Daniel 1960- (Oxford University Press, 2014)
The remarkable story of how the Allies used psychoanalysis to delve into the motivations of the Nazi leadership and to explore the mass psychology of fascism